Alyzon Whitestarr - Carmody, Isobelle. frey50 (New York : Random House, 2009)
When Alyzon, the ordinary member of an extraordinary family, develops enhanced senses, she becomes aware of an evil virus that preys on people's spirits, and realizes that the sickness and its disseminators are aware of her and are a menace to her family.
Keywords: Psychic ability; Families -- Australia; Paranormal fiction; Psychic ability; Virus diseases; Family life -- Australia; Senses and sensation; Supernatural; Eccentrics and eccentricities; Australia; Australia; Young adult fiction